Optimalisasi Pompa Air Berbasis Teknologi Tepat Guna Mendukung Pemulihan Air Bersih Pascabencana Aceh Tamiang - Agus Putra AS; Fairus Fairus; Afrah Junita (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
This community service activity was carried out in Simpang Lhee Village, Manyak Payed District, Aceh Tamiang Regency as an effort to restore clean water access after the flash flood disaster that caused damage to community water sources. This program aims to provide clean water access through the optimization of water pumps based on appropriate technology that is easy to operate and sustainable. The implementation method was carried out in a participatory manner through stages of socialization, training, technology application, mentoring, and evaluation. The activity was attended by 35 participants consisting of the community, village officials, students, and lecturers. The results of the activity showed that the installation of water pumps succeeded in providing more stable clean water access for the affected community with a service capacity reaching around 520 people or a clean water need of ± 7,800–10,400 liters per day. In addition, there was an increase in community capacity in managing clean water facilities, demonstrated by increased knowledge of clean and healthy living behaviors, the ability to operate water pumps independently, and the formation of village clean water management groups. The evaluation results showed that all community empowerment indicators were in the high category with a percentage of 80%–84%. This program is considered effective in reducing dependence on external aid, reducing the risk of water-based diseases, and strengthening community independence in facing future disasters.